Comparison of tolerability between quetiapine and haloperidol in schizophrenia - Koirala, Naba Raj; Chapagain, Manisha; Tulachan, Pratikchya; Zafreen, Siquafa (Journal of Nobel Medical College, 2012)
Schizophrenia is a serious, disabling, often lifetime condition, which can produce severe functional impairment in patients. The life time morbidity risk for schizophrenia is estimated to be 1% and account for 2.8% of the total global YLDs. The World Health Organization Assessment Instrument for Mental Health Systems report of 2006 done in Nepal states in Nepal states that 12% of the patients are diagnosed as schizophrenia in out-patient mental facilities, 14% in community based psychiatry inpatient units and 34% in mental hospital. Atypical antipsychotics are the first line agents recommended for the treatment of schizophrenia considering better efficacy at least in the negative symptoms and better side-effect profile compared with typical antipsychotic. Haloperidol has been used as a standard comparator in numerous trials and new drugs have been compared to it to establish their efficacy, and safety profile. As the authors could not find out any such study which had compared the safety profile of quetipine against conventional antipsychotic, hence this present study is purposed to carry as an attempt to address this issue among Nepalese population.DOI: http://dx.doi.org/10.3126/jonmc.v1i1.7289 Journal of Nobel Medical College Vol.1(1) 2011 59-64